2021
DOI: 10.3390/microorganisms9091793
|View full text |Cite
|
Sign up to set email alerts
|

The Intestinal Bacterial Community and Functional Potential of Litopenaeus vannamei in the Coastal Areas of China

Abstract: Intestinal bacteria are crucial for the healthy aquaculture of Litopenaeus vannamei, and the coastal areas of China are important areas for concentrated L. vannamei cultivation. In this study, we evaluated different compositions and structures, key roles, and functional potentials of the intestinal bacterial community of L. vannamei shrimp collected in 12 Chinese coastal cities and investigated the correlation between the intestinal bacteria and functional potentials. The dominant bacteria in the shrimp intest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 84 publications
(132 reference statements)
1
2
0
Order By: Relevance
“…The analysis of species' relative abundance in the disinfectant groups and the control group showed that, at the phylum level, the dominant microflora were Proteobacteria, Firmicutes, Actinobacteria, Bacteroidetes, and Cyanobacteria, among which Proteobacteria had the largest relative abundance, which was similar to the results of previous studies (Fan et al, 2019;Cheng et al, 2021). At the genus level, the dominant bacterial genera in the intestinal bacterial community of L. vannamei were Photobacterium, Vibrio, and Ruegeria.…”
Section: Discussionsupporting
confidence: 86%
“…The analysis of species' relative abundance in the disinfectant groups and the control group showed that, at the phylum level, the dominant microflora were Proteobacteria, Firmicutes, Actinobacteria, Bacteroidetes, and Cyanobacteria, among which Proteobacteria had the largest relative abundance, which was similar to the results of previous studies (Fan et al, 2019;Cheng et al, 2021). At the genus level, the dominant bacterial genera in the intestinal bacterial community of L. vannamei were Photobacterium, Vibrio, and Ruegeria.…”
Section: Discussionsupporting
confidence: 86%
“…At the genus level (Figure 3c), the bacterial species initially found in shrimp samples were Ralstonia, Vibrio and Aliivibrio. These genera are known to originate from the intestinal tract of Penaeus vannamei, according to previous studies [48]. In group B, the dominant bacteria were Ralstonia, Alivibrio, Photobacterium, Moritella and Pseudoalteromonas.…”
Section: Species Annotation and Composition Analysismentioning
confidence: 82%
“…Thus, studying the potential, resident, and beneficial microbes is crucial for improving host health. To date, several amplicon sequence-based studies on P. vannamei have characterized the microbial communities in different habitats [ 6 ], developmental stages [ 6 ], disease conditions [ 59 ], and diet [ 47 ].…”
Section: Introductionmentioning
confidence: 99%